Adding shooting intervals to the 20 m multistage shuttle run test; a new test “shooting shuttle run test” - Karatas, Mustafa; Dogan, Ali Ahmet (Progress in Nutrition, 2022)
This study aims to develop a new test by modifying the 20 m multi-stage shuttle run test, in which shooting intervals are added. 137 male police candidates (20.91±1.19 years, height 177.42±6.02 cm, body weight 72.26±8.51 kg, body mass index 22.92±2.15 kg/m2) who were studying at Police Vocational School participated in the study voluntarily. The 20-meter multi-stage shuttle run test has been modified and a 3-second shooting interval has been added to each level. Police candidates were first subjected to the multistage shuttle run test. They participated in the shooting shuttle run test one week later and the retest one week later. In the measurements, the mean heart rate and the number of completed shuttles were recorded. In the reliability analysis, the Intraclass Correlation Coefficient (ICC) of the Test-Retest data was calculated. In the validity analysis, The Concurrent Validity test was applied to the results of the original shuttle run test and the shooting shuttle run test, and the Pearson Correlation coefficient was used. As a result of the reliability analysis, a significant correlation was found in the completed shuttle (ICC r=0.99, p<0.01) and heart rate data (ICC r=0.95, p<0.01) of the test-retest measurements. As a result of the validity analysis, a significant correlation was found in the completed Shuttle (r=0.93, p<0.01) and heart rate data (r=0.90, p<0.01) of the shuttle run test and shooting shuttle run test measurements. As a result, it has been determined that the shooting shuttle run test, in which 3 seconds of shooting intervals are added, has a high level of reliability and validity. It can be said that the shooting shuttle run test can be used to simultaneously measure the shooting performance and endurance of police and security forces. It is recommended to use the shooting shuttle run test in all sports involving shooting, where shooting performance is important, and in sports such as football, basketball and handball.